La Spada dell’Islam: the Maghrebian Reaction to Fascist Subversion of the Inter-War Period - Kaitlyn Rabe (The Journal of Undergraduate Research, 2016)
Both academic and popular writers tend to agree that Italian fascism failed in expanding internationally, especially in regards to Italian military actions in Libya. Enough evidence exists, however, to conclude that Italian fascist subversion helped to spread Mussolini’s “empire” in an unexpected way: by directly contributing to the rise of fascist-appropriating social movements in the 1930s in certain Maghrebian countries, namely Tunisia and Egypt. The Tunisian anticolonial movement, for example, is not traditionally viewed as being strictly “fascist”, but upon comparing its’ elites’ views—especially those elites with subversive connections to the fascist regime—to those expressed by Mussolini and his officials it becomes clear that Tunisian elites were indeed at least appropriating aspects of fascism. Egyptian student groups as well were particularly important in openly appropriating aspects of Italian fascism. In Libya, however, fascism was highly unpopular and Italian military actions there actually damaged fascism’s reputation in the Arab world in general. Given the outcomes of Italian fascist interference in these three countries, my project answers the following questions: what was fascism, a European-born movement, doing in the Arab world? Why was it allowed to exist in Tunisia and Egypt but pushed out so vehemently in Libya? And what tangible effects did the influence of fascism have on the regimes of Egypt, Tunisia, and Libya? Therefore, by using the interference of Italian fascism as a sort of case study, my project demonstrates that the nationalist movements in each respective country were the largest impetus in movements that interacted with European systems, and were actually more significant than the Pan-Arab movement. The nationalist movements of the Maghreb, therefore, were neither “pro-Europe” nor “anti-Europe”, but rather could utilize aspects of whatever European system seemed most beneficial, which, to Tunisian and Egyptian elites, was fascism.